THE INFLUENCE OF EDUCATIONAL BACKGROUND, FINANCIAL LITERACY, AND FINANCIAL PLANNING ON THE FINANCIAL BEHAVIOR OF MSME (CASE STUDY IN MSMES IN THE JAMBANGAN SUB-DISTRICT, SURABAYA CITY) - Lesmana, Arya Widi; Hidayat, Sjarief (Yayasan Education and Social Center, 2023)
This study assessed how educational background, financial literacy, and financial planning impact the financial behaviour of MSMEs in the Jambangan Sub-District of Surabaya City. The study encompassed a total population of 969 MSMEs in this area. Quantitative research methods were employed, with data analysis conducted using Partial Least Squares. Data collection involved a questionnaire consisting of 17 questions. The sample criteria for this research were MSMEs engaged in financial planning and employing a minimum of 2 individuals, resulting in a sample size of 44 MSMEs in the Jambangan Sub-District of Surabaya City. The study's findings indicate that educational background, financial literacy, and financial planning positively and significantly influence the financial behaviour of MSMEs in the Jambangan Sub-District of Surabaya City